(untitled) (British Journal of Global Ecology and Sustainable Development, 2022)
Today moniliosis or fruit rot disease is a very common and harmful disease of seed fruits. It appears in the form of a brown tint and rot of fruits, but is the cause of the death of the inflorescences and other organs of the plant. Today, the moniliosis disease of apples, like a number of diseases in the supply of axoli with quality seedmevas, causes serious harm to ham. Our research goal is to qualitatively protect the Apple plant from this disease.